Beyond borders: the dynamic role of Papuan Muslims in governing special autonomy - Darus, Muhammad Rifai; Abdullah, Irwan; Qodir, Zuly; Jubba, Hasse (Department of Government Studies, Universitas Muhammadiyah Makassar, 2024)
The implementation of special autonomy in Papua Province has raised critical challenges, particularly the marginalization of certain groups based on ethnicity and religion. This study examines the dynamic role of Muslim groups in Papua post-special autonomy implementation, addressing gaps in previous research. Using a qualitative descriptive case study approach, the findings reveal three key points. First, the political engagement of Muslim groups has become more dynamic but remains limited compared to Indigenous Papuans (OAP). Second, special autonomy policies, while intended to empower OAPs, have narrowed the participation space for non-OAP groups, including Muslims. Third, the policies restrict opportunities for Muslim Papuans to hold strategic government positions, as recruitment prioritizes OAP representation. These findings highlight the multidimensional challenges of special autonomy, including social, political, and economic inequalities. The study concludes that, while special autonomy policies offer opportunities for regional development, they also foster tensions and marginalization. To address these issues, it recommends adopting more inclusive governance and balanced policies that accommodate both OAP and non-OAP groups. By doing so, Papua’s development can be more equitable and sustainable, fostering harmony among its diverse communities.